2005
DOI: 10.1007/s11920-005-0069-5
|View full text |Cite
|
Sign up to set email alerts
|

The burden of general medical conditions in patients with bipolar disorder

Abstract: We reviewed the current literature on medical comorbidity burden in bipolar disorder. Overall, current studies suggest that numerous medical conditions may occur disproportionately within bipolar disorder patient populations, including hypertension, hyperlipidemia, and hepatitis C infection. In addition, the determinants of increased burden of medical comorbidity in patients with bipolar disorder include metabolic-related factors, health care access barriers, and patient behavioral and treatment factors. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 48 publications
3
22
1
Order By: Relevance
“…Beyer and colleagues (2005) found high rates of hypertension, cardiovascular disorders, COPD/asthma, diabetes, and HIV infection in a sample of 1379 patients with bipolar disorder who received treatment in an outpatient psychiatric clinic. Similarly, Kilbourne (2005) found high rates of hypertension, hyperlipidemia, and hepatitis C (HCV) infection among those diagnosed with bipolar disorder. The estimated prevalence of Type 2 diabetes among individuals with bipolar disorder is 17% (Kilbourne, 2005), compared to 7% of the general population (American Diabetes Association, 2006).…”
Section: Mood Disorders and Medical Illnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyer and colleagues (2005) found high rates of hypertension, cardiovascular disorders, COPD/asthma, diabetes, and HIV infection in a sample of 1379 patients with bipolar disorder who received treatment in an outpatient psychiatric clinic. Similarly, Kilbourne (2005) found high rates of hypertension, hyperlipidemia, and hepatitis C (HCV) infection among those diagnosed with bipolar disorder. The estimated prevalence of Type 2 diabetes among individuals with bipolar disorder is 17% (Kilbourne, 2005), compared to 7% of the general population (American Diabetes Association, 2006).…”
Section: Mood Disorders and Medical Illnessmentioning
confidence: 99%
“…Similarly, Kilbourne (2005) found high rates of hypertension, hyperlipidemia, and hepatitis C (HCV) infection among those diagnosed with bipolar disorder. The estimated prevalence of Type 2 diabetes among individuals with bipolar disorder is 17% (Kilbourne, 2005), compared to 7% of the general population (American Diabetes Association, 2006). Similarly to those with depression, individuals with comorbid bipolar disorder often receive inadequate treatment for medical illnesses; in a study of 248 patients with bipolar disorder over age 50, 25% received a flu vaccine, and 33% of those prescribed divalproex received a hepatic function test (Kilbourne, 2005).…”
Section: Mood Disorders and Medical Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization lists bipolar disorder seventh for overall disease burden across all medical or psychiatric conditions (Murray and Lopez 1996). These patients experience a substantial number of attendant physical and mental health comorbidities, social and occupational instability, and high relapse rates even when consistently engaged in appropriate psychosocial management or maintenance pharmacotherapy (Kilbourne 2005;Miller et al 2004). Furthermore, certain subgroups may present with unique clinical factors or vulnerabilities requiring particular treatment considerations, such as female or ethnic minority populations (Kilbourne et al 2005a;Marangell 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is unclear whether any such age-related decline reflects the additive effect of normal age-related cognitive changes, it is suggested that accumulation of affective episodes may result in greater neurocognitive impairment (6). Older patients are also prone to higher numbers of co-morbid medical conditions, and the parallel polypharmacy; thus, are more likely to have complex medication management regimens while having fewer cognitive resources (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%